Saharan warm-air intrusions in the western Mediterranean: identification, impacts on temperature extremes, and large-scale mechanisms - P. Cos; P. Cos; M. Olmo; D. Campos; D. Campos; R. Marcos-Matamoros; L. Palma; L. Palma; Á. G. Muñoz; F. J. Doblas-Reyes; F. J. Doblas-Reyes (Weather and Climate Dynamics)
Saharan warm intrusions are air masses that develop over the Sahara and that can be advected into surrounding areas, creating anomalous atmospheric conditions in those regions. This paper focuses on the characteristics of these intrusions into the western Mediterranean (WMed) region and their relationship with extreme temperatures in the neighbouring areas during the recent past (1959–2022). We describe and evaluate a methodology to identify Saharan air masses throughout the year, and, consequently, a historical catalogue of intrusion events that reach the WMed is built. To identify which large-scale phenomena might be relevant for the formation of the intrusions, we first identify different intrusion types (ITs) through a clustering procedure. Different ITs are found for the four seasons, which discriminate between the intrusions according to their longitudinal position over the Mediterranean region and their intensity. Upper-tropospheric anomalies are linked to the onset of these events, in particular an anomalous geopotential high over the intrusion region that slows down the upper-tropospheric circulation over northern Africa. These events are very relevant as they impact extreme temperatures throughout the year and account for a high percentage of the extreme-temperature events recorded in the WMed and neighbouring regions in summer.